Effects of concurrent and staggered dosing of semi-solid enteral nutrients on pharmacokinetic behavior of antiepileptic drugs after oral administration in rats - Katsuhito Nagai (Public Library of Science (PLoS), 2021)
Background The use of enteral nutrients plays a highly important role in accurate nutrition management, but limited information is currently available on the cautionary points of semi-solid enteral nutrients. Aim In this study, we examined whether the pharmacokinetic profiles of sodium valproate (SVA), levetiracetam (LEV), and carbamazepine (CBZ) are affected by altering the dosing time of RACOL®-NF Semi Solid for Enteral Use (RASS), a prescribed semi-solid formula. We also investigated whether the pharmacokinetic interaction observed in this study can be avoided by staggered dosing of the chemical drug and semi-solid enteral nutrient. Methods The plasma concentration of SVA, LEV and CBZ after oral administration was measured by LC-MS/MS method. Results There was no difference in pharmacokinetic characteristics of SVA and LEV when the dosing time of RASS was altered. On the other hand, the plasma concentration of CBZ after oral administration at all sampling points decreased with the extension of the dosing time of RASS, which was consistent with the Cmax and AUC. However, no significant difference was observed in the pharmacokinetic profiles or parameters of CBZ between the short-term and long-term RASS dosing groups by prolonging the administered interval of CBZ and RASS for 2 hr. Conclusion We concluded that the pharmacokinetic profiles of CBZ, but not SVA and LEV, after its oral administration are affected by the dosing time of RASS, but staggered administration of CBZ and RASS prevented their interaction.